2022
DOI: 10.1002/tal.1988
|View full text |Cite
|
Sign up to set email alerts
|

Tensile behavior of cruciform stubs with four bolts per row

Abstract: The stiffened top-and-seat angle connection is widely used in earthquake-prone areas, and additional tensile bolts on angles' column leg effectively improve its bending behavior. However, such design and construction are not governed by any regulations. It is urgent to figure out the mechanical behavior and develop accurate theoretical methods. Based on the component method, this paper first conducted an experimental study on the extracted cruciform stubs with four bolts per row. It compared the tensile proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The result from the study makes it feasible to specify the angle thickness and bolt type in practical design, and it would be preferable to have an initial stiffness calculation method with stiffeners having a staggered bolt pattern [25]. In another study, where a cruciform stub with four bolts in a row was proposed, it was concluded that the stub thickness and bolt gauge impact the plastic resistance more than the bolt spacing [26]. The different layouts, in-line, rectangular, and circular, were studied to minimize the tensile stresses in the T-stub connections.…”
Section: Optimization Of Bolt Layoutmentioning
confidence: 99%
“…The result from the study makes it feasible to specify the angle thickness and bolt type in practical design, and it would be preferable to have an initial stiffness calculation method with stiffeners having a staggered bolt pattern [25]. In another study, where a cruciform stub with four bolts in a row was proposed, it was concluded that the stub thickness and bolt gauge impact the plastic resistance more than the bolt spacing [26]. The different layouts, in-line, rectangular, and circular, were studied to minimize the tensile stresses in the T-stub connections.…”
Section: Optimization Of Bolt Layoutmentioning
confidence: 99%